Biotechnology techniques for the development of new tumor specific peptides - Marr, Annabell; Markert, Annette; Altmann, Annette; Askoxylakis, Vasileios; Haberkorn, Uwe (Methods, 2011)
Peptides, proteins and antibodies are promising candidates as carriers for radionuclides in endoradiotherapy. This novel class of pharmaceuticals offers a great potential for the targeted therapy of cancer. The fact that some receptors are overexpressed in several tumor types and can be targeted by small peptides, proteins or antibodies conjugated to radionuclides has been used in the past for the development of peptide endoradiotherapeutic agents such as 90Y-DOTATOC or radioimmunotherapy of lymphomas with Zevalin. These procedures have been shown to be powerful options for the treatment of cancer patients. Design of new peptide libraries and scaffolds combined with biopanning techniques like phage and ribosome display may lead to the discovery of new specific ligands for target structures overexpressed in malignant tumors. Display methods are high throughput systems which select for high affinity binders. These methods allow the screening of a vast amount of potential binding motifs which may be exposed to either cells overexpressing the target structures or in a cell-free system to the protein itself. Labelling these binders with radionuclides creates new potential tracers for application in diagnosis and endoradiotherapy. This review highlights the advantages and problems of phage and ribosome display for the identification and evaluation of new tumor specific peptides.